Strengthening Smart Specialisation Strategies (S3) through network analysis: Policy insights from a decade of innovation projects in Aragón - David Rodríguez Ochoa; Nieves Arranz; M. F. Arroyabe (Economies, 2025)
This paper applies a multi-level social network analysis to examine Aragón's innovation ecosystem, focusing on a decade of competitive public projects (2014-2023) aligned with the region's Smart Specialisation Strategy (S3) 2021-2027. By mapping and weighting the participation of regional entities across regional, national, and European calls, the study uncovers how all types of local actors organise themselves around key specialisation areas. Moreover, a comparative benchmark is introduced by analysing more than 33,000 Horizon 2020 and Horizon Europe initiatives without Aragonese partners, revealing how to fill structural gaps and enrich the regional ecosystem through international collaboration. Results show strong funding concentration in four fields-Energy, Health, Agri-Food, and Advanced Technologies-while other historically strategic areas like Hydrogen and Water remain underrepresented. Although leading institutions (UNIZAR, CIRCE, ITA, AITIIP) play central roles in connecting academia and industry, direct collaboration among them is limited, pointing to missed synergies. Expanding previous SNA-based assessments, this study introduces a diagnostic tool to guide policy, proposing targeted actions such as challenge-driven calls, dedicated support programs, and cross-border consortia with top EU partners. Applied to two contrasting specialisation areas, the method offers sector-specific recommendations, helping policymakers align Aragón's innovation capabilities with EU priorities and strengthen its position in both established and emerging domains.
Keywords: 330; Aragon; competitive public projects; innovation ecosystem; regional innovation; smart specialisation strategy; social network analysis